Formulasi dan Uji Aktivitas Antioksidan Sediaan Face Toner Ekstrak Daun Pandan Wangi (Pandanus amaryllifolius Roxb.) Menggunakan Metode DPPH - Rahmadini Rahmadini; Alfina Nurrahman; Kharisma Jayak Pratama (Journal of Innovative and Creativity, 2026)
ABSTRACT Free radicals are unstable molecules that can damage cell membranes, DNA, and proteins, thereby triggering premature aging. Preventive efforts can be carried out through skin care using cosmetic products containing natural antioxidants, which are considered safer and capable of providing long-term protection. One cosmetic product that functions as a moisturizer is face toner. Fragrant pandan leaves (Pandanus amaryllifolius Roxb.) are known to contain antioxidant compounds, making them potential active ingredients in face toner formulations. This study aimed to formulate a face toner containing fragrant pandan leaf extract in three concentration variations, namely 1%, 2%, and 3%. Antioxidant activity was evaluated using the DPPH method to determine IC₅₀ values. Physical quality evaluations were also conducted, including organoleptic tests, homogeneity, pH, and viscosity. The results showed that formula 0 had an IC₅₀ value of 261.11 ppm (very weak), formula 1 had an IC₅₀ value of 51.95 ppm (strong), formula 2 had an IC₅₀ value of 40.32 ppm (very strong), and formula 3 had an IC₅₀ value of 32.91 ppm (very strong). In addition, all formulations (0%, 1%, 2%, and 3%) met the physical quality requirements for cosmetic preparations. Keywords: Antioxidant, Fragrant Pandan Leaves, Extract, Face toner